Determinan Pemanfaatan Program Pengelolaan Penyakit Kronis (PROLANIS) di Wilayah Kerja Puskesmas Talang Banjar Kota Jambi - Inggani, Della; Solida, Adila; Hubaybah, Hubaybah (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2024)
AbstractBackground: Talang Banjar Community Health Center is a community health center with the lowest Controlled Prolanist Participant Ratio (RPPT) in Jambi City, namely 0.55% from â‰¥ 5% set by BPJS. Of the 185 patients diagnosed with diabetes mellitus, only 39 patients were registered as pronalis participants and only 1 patient was controlled on prolanis. Meanwhile, of the 658 diagnosed with hypertension, 36 patients were registered as pronalis participants and only 3 patients were controlled on prolanis. Researchers aim to analyze the determinants of utilization of the chronic disease management program (prolanis) in the working area of the Talang Banjar Community Health Center, Jambi City.Research Method: This type of research is quantitative research with a cross sectional study design. The total population in this study was 75 respondents. The sample in this study was selected using the Total Sampling Technique, namely all prolanis participants who were registered at the Talang Banjar Community Health Center, Jambi City. The dependent variable was the use of prolanis and the independent variables were age, gender, education, employment, knowledge, accessibility, attitude of health workers, and perception of disease. Data analysis used the chi square test.Research Results: There is a relationship between education (p = 0,049), knowledge (p = 0,000), accessibility (p = 0,043), and perception of disease (0,020) with the use of prolanis. There was no relationship between age (p = 0,254), gender (p = 0,383), occupation (p = 1,000), and attitude of health workers (p = 0,320) with the use of prolanis.Conclusion: There is a relationship between education, knowledge, accessibility and perception of disease with the use of prolanis. There is no relationship between age, gender, occupation and attitude of health workers with the use of prolanis.Keywords: Determinants, Utilization of Prolanis, Diabetes Mellitus, Hypertension and Prolanis BPJS Health Participants